Proceedings of the international symposium on islamic civilisation in the Volga-Ural Region : Kazan, 8-11 June 2001 = Dokladı mejdunarodnoy konferentsii islamskaya kultura v Volga-Uralskom Regione : Kazan, 8-11 İyunya 2001 g. (İstanbul)
xxxii, 379 s.